2017
DOI: 10.5312/wjo.v8.i5.424
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for calcifying tendinitis of the shoulder: A systematic review

Abstract: AIMTo systematically search literature and determine a preferable surgical procedure in patients with failed conservative treatment of calcifying tendinitis of the shoulder.METHODSThe electronic online databases MEDLINE (through PubMed), EMBASE (through OVID), CINAHL (through EB- SCO), Web of Science and Cochrane Central Register of Controlled Trials were systematically searched in May 2016. Eligible for inclusion were all available studies with level II and level III evidence (LoE). Data was assessed and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…Ultrasound-assisted needling is often used to treat calcific tendinitis because it can be performed at a relatively low cost under local anesthesia on an outpatient basis. One recent systematic review [ 12 ] showed that there is a large variation between studies using ultrasound-assisted needling, thus additional high-quality studies are required for low-quality evidence. ESWT has been used as a treatment for calcific tendinitis since the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-assisted needling is often used to treat calcific tendinitis because it can be performed at a relatively low cost under local anesthesia on an outpatient basis. One recent systematic review [ 12 ] showed that there is a large variation between studies using ultrasound-assisted needling, thus additional high-quality studies are required for low-quality evidence. ESWT has been used as a treatment for calcific tendinitis since the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…A current literature search [31] analyzed all the articles listed in Medline, Embase, Cinahl, and Cochrane on this subjectand outof574 publications, found only 6 LoE II or III studies in which comparisons were undertaken between individual surgical procedures, but not a single study with an untreated control group. The subjective and functional success rate was between 73 and 80% with all procedures studied.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…Table 2). Verstraelen [31] concludes that there is no relationship between CT and subacromial impingement.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…It is demonstrated that even interventional or minor surgical procedures may be associated with a significant psychological burden in patients, potentially generating discomfort and anxiety [14]. Regarding US-PICT, the procedure is generally performed with 16-to 21-gauge needles under local anesthesia.…”
Section: Introductionmentioning
confidence: 99%